ANALISIS FILM KARTUN UPIN IPIN DALAM MENANAMKAN NILAI-NILAI PENDIDIKAN KARAKTER SISWA KELAS 2 DI SD ISLAM PLUS AR-RASHEED INDONESIA - Rizal Kailani; Said Denni Kurniawan; Sudeni (PT. IHLAS (Ilmu Adalah Segalanya) - BICARA CENTRE, 2026)
Education is part of human life. Since in the womb and at birth, they have received education from the people around them, especially their parents. It is undeniable that every day we will interact with other humans and with the environment. The existence of this interaction fosters various values ​​and cultures in life that form an educational process. This research includes literature review research or literature study, which contains theories related to research problems. The type of research used in this study is library research, which is research conducted by collecting data or scientific papers aimed at research objects or data collection that is library in nature. Educational media is an important part used in the world of education. The development of educational media is in line with the development of technology that makes it easier for people to receive information quickly and is not limited by space and time. One type of educational media is the Upin Ipin cartoon film. In the Upin Ipin cartoon film, there are character education values ​​contained in it and it is hoped that they can be instilled in students in grade 2 of SD Islam Plus Ar-Rasheed Indonesia. One of the Upin and Ipin animated films contains many character education values ​​that are embedded in every part of the story. This film made by the neighboring country received a very positive response in various countries including Indonesia. So far, society has assumed that many functions of films are merely entertainment, therefore this assumption must be changed, and film media must be made into an educational medium by taking the wisdom and messages that are written or implied in the film.